2017
DOI: 10.1080/0284186x.2017.1299936
|View full text |Cite
|
Sign up to set email alerts
|

Interfractional renal and diaphragmatic position variation during radiotherapy in children and adults: is there a difference?

Abstract: Interfractional renal and diaphragmatic position variation in children is smaller than in adults indicating that pediatric margins should be defined differently from adult margins. Underlying mechanisms and other components of geometrical uncertainties need further investigation to explain differences and to appropriately define pediatric safety margins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…180-760) between children and adults. However, for each patient, a sufficient amount of projection images was available for tracking diaphragm motion, representing sufficient breathing cycles (approximately 10-30) for the calculation of our parameters.Although the differences in respiratory motion characteristics between children and adults are smaller, our present results on intrafractional organ motion are in line with findings from our previous study, in which we demonstrated that interfractional abdominal organ motion in children differed from that in adults 33. This underscores the need, also in children, for a more individualized approach using 4DCT to define safety margins.…”
supporting
confidence: 92%
“…180-760) between children and adults. However, for each patient, a sufficient amount of projection images was available for tracking diaphragm motion, representing sufficient breathing cycles (approximately 10-30) for the calculation of our parameters.Although the differences in respiratory motion characteristics between children and adults are smaller, our present results on intrafractional organ motion are in line with findings from our previous study, in which we demonstrated that interfractional abdominal organ motion in children differed from that in adults 33. This underscores the need, also in children, for a more individualized approach using 4DCT to define safety margins.…”
supporting
confidence: 92%
“…Motion and/or patient set-up uncertainties have already been studied for abdominal tumors in adults [8][9][10] and in children [11][12][13][14][15][16][17][18]. Four-dimensional computed tomography (4D-CT) [11,12] and 4D magnetic resonance imaging (MRI) [13] are used to estimate the breathing uncertainty and daily cone-beam CT-scans (CBCT) are used to assess both intra-and inter-fraction uncertainties [14][15][16][17][18]. However, none of these studies with pediatric patients has investigated both intraand inter-fraction TB and OAR motion and patient set-up uncertainties for a homogeneous disease patient cohort at a single institute.…”
Section: Introductionmentioning
confidence: 99%
“…Van Dijk et al analyzed 850 CBCT datasets of 35 children and 35 adults treated with thoracic/abdominal RT to determine pediatric safety margins. 15 Interfractional diaphragm position errors were 2.1, 9.9, and 4.9 mm (M, Σ, and σ, respectively) in the SI direction for adults. Variations in diaphragm position in the other directions were not measured.…”
Section: Discussionmentioning
confidence: 88%
“…The authors suggested that differences in daily breath‐holding had a large effect on interfractional diaphragm changes. Van Dijk et al analyzed 850 CBCT datasets of 35 children and 35 adults treated with thoracic/abdominal RT to determine pediatric safety margins 15 . Interfractional diaphragm position errors were 2.1, 9.9, and 4.9 mm (M, Σ, and σ, respectively) in the SI direction for adults.…”
Section: Discussionmentioning
confidence: 99%